MO130: Effect of Long-Term Low Protein Diet Use at Myocardium Remodelling in Rats With Experimental Decrease of Working Nephrons Weight. (3rd May 2022) - Beresneva, Olga; Parastaeva, Marina; Ivanova, Galina; Khasun, Mokhamad; Kucher, Anatoly; Kayukov, Ivan; Rumyantsev, Aleksander
Abstract: BACKGROUND AND AIMS: Cardiovascular disturbances are the most frequent cause of death in patients with chronic kidney disease (CKD). Various options of low protein diets (LPD) are widely used in CKD treatment. However, their role in cardioprotection at CKD is understudied. The aim was to study the features of myocardium remodelling in Wistar rats for a long period post-nephrectomy (NE), who received LPD that included 10% of the complex of indispensable amino acids and their keto analogues. METHOD: The study was carried out on adult (2.5–3 months) Wistar male rats. The control group (C) consisted of 9 sham operated (SO) rats; the second group consisted of 8 animals, in whom the resection of 5/6 kidney tissue (NE) was performed with the purpose to create the renal dysfunction model. The rats from these two groups received the standard feed, containing 20.16% of animal protein. The rats from the third group (n = 12) received LPD that included 10% of the complex of indispensable amino acids and their keto analogues (Ketosteril, Fresenius Kabi, Germany) after 5/6 NE. Four months after NE, blood pressure (BP, mm Hg) was measured in the animals. The left ventricular muscle mass index (LVMMI) was calculated as a ratio of LV weight/body weight (mg/g). The morphological changes of the myocardium were evaluated by quantitative morphometry using VideoTest 5.2. Results are presented as mean ± SD. The Student's t-test and the Mann–Whitney test were used for statistical analysis. RESULTS: In 4 months, the average BP level in the C group was 130 ± 5 mm Hg; in rats with NE on the standard diet, it was 158.7 ± 11.0 mm Hg, and in animals on LPD 130 ± 12.8 mm Hg ( P < .001). In rats with NE on the standard diet, LVMMI (2.72 ± 0.11) was higher than in the C group (2.35 ± 0.09, P < .01). In rats with NE that received LPD, there was no significant change in this indicator versus the C group ( P > .05). In rats with NE against LPD administration, the cardiocytes thickness (9.5 ± 1.9 µm) and the cardiocytes nuclei area (26.6 ± 4.7 µm 2 ) decreased, the ratio of cardiocytes nuclei area and cardiocytes thickness (0.38 ± 0.14) versus animals at the standard diet (14.19 ± 0.08, µm; 34.1 ± 8.1 µm 2 ; and 0.23 ± 0.03; P < .001 in all cases) increased. In the NE group on LPD, the number of polynuclear cardiocytes was less than (0.3%) versus the NE group on the standard diet (1%). The connective tissue area indicator was 2837.6 ± 1263.1 µm 2 versus 4008.1 ± 2185.7 µm 2 ( P = .061) in rats that received common feed. The decrease in ratio of capillaries area (%)/cardiocytes area (%) in rats on LPD, more than two times versus the NE group on standard diet, was noted. This is mostly conditioned by decrease in area occupied by connective tissue to 12% (2837.60 ± 1263.19 µm 2 ) and decrease in total capillaries cross section up to 5% (1061.1 ± 78.3 µm 2 ) in rats with LPD. The decrease of perivascular fibrosis degree in animals on LPD was determined. However, the vessel wall thickness in the NE groups (NE + LPD and NE on standard diet 29.9 ± 7 µm and 26.4 ± 17.6 µm; р = 0.211, respectively) increases versus C group (17.6 ± 5.1; P = .03). CONCLUSION: The use of LPD in rats with NE has a cardioprotective effect, inhibiting the BP increase and the LVMMI index growth. In terms of histology, this was expressed through the decrease of cardiocyte hypertrophy degree, decrease in nuclei area, decrease of nucleoplasmic ratio, diffuse and perivascular sclerosis area.